Placement of Surgical Feeding Tubes Among Patients With Severe Traumatic Brain Injury Requiring Exploratory Abdominal Surgery: Better Early Than Late. Issue 6 (June 2020) - Cha, Peter I.; Jou, Ronald M.; Spain, David A.; Forrester, Joseph D.
Objectives: The purpose of this study was to identify trauma patients who would benefit from surgical placement of an enteral feeding tube during their index abdominal trauma operation. Methods: We performed a retrospective analysis of all patients admitted to 2 level I trauma centers between January 2013 and February 2018 requiring urgent exploratory abdominal surgery. Results: Six-hundred and one patients required exploratory abdominal surgery within 24 hours of admission after trauma activation. Nineteen (3% of total) patients underwent placement of a feeding tube after their initial exploratory surgery. On multivariate analysis, an intracranial Abbreviated Injury Scale ≥4 (odds ratio [OR] = 9.24, 95% CI 1.09-78.26, P = .04) and a Glasgow Coma Scale ≤8 (OR = 4.39, 95% CI 1.38-13.95, P = .01) were associated with increased odds of requiring a feeding tube. All patients who required a feeding tube had an Injury Severity Score ≥15. While not statistically significant, patients with an open surgical feeding tube compared with interventional radiology/percutaneous endoscopic gastrostomy placement had lower median intensive care unit length of stay, fewer ventilator days, and shorter median total hospital length of stay. Conclusions: Trauma patients with severe intracranial injury already requiring urgent exploratory abdominal surgery may benefit from early, concomitant placement of a feeding tube during the index abdominal operation, or at fascial closure.